Oculodentodigital Dysplasia Presenting as Spastic Ataxic Syndrome in an Indian Patient - Gosala RK Sarma; Abhinaya Varidireddy; GG Sharath; Sunitha P Kumaran (Annals of Indian Academy of Neurology, 2025)
Spastic ataxic syndrome is a combination of cerebellar ataxia with spasticity and other pyramidal features. Common causes of spastic ataxic syndrome include spinocerebellar ataxia (SCA) 1, SCA2, autosomal recessive ataxia of Charlevoix–Saguenay, Friedreich ataxia, and hereditary spastic paraplegia type-7. We report a 32-year-old female who presented with unsteadiness of gait, incoordination, and tremulousness of both hands for 10 years with microphthalmia, microdontia, dental caries, and syndactyly. Magnetic resonance imaging of the brain showed T2 fluid-attenuated inversion recovery hyper intensities in periventricular and lobar white matter and internal capsule. Thus, we report a genetically confirmed oculodentodigital dysplasia (ODDD), an autosomal dominant disorder, in an Indian patient who presented with spastic ataxic syndrome, a rarity that has not been reported so far.